2014
DOI: 10.3390/molecules191221127
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Inflammatory Bowel Disease: Potential and Limits of Innovative Treatments

Abstract: Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 177 publications
(176 reference statements)
0
54
0
Order By: Relevance
“…Novel therapies, including TNFneutralizing antibodies, have demonstrated efficacy in improving mucosal healing, but their side effects and toxicity remain major clinical concerns (21). Therefore, the development of medicinal plants or their active components with minimum adverse reactions is becoming an increasingly attractive approach in the management of IBD patients (26,27). Chalcones belong to the flavonoid family, which possess a variety of biological and pharmacological properties, including antioxidant, cytotoxic, anti-cancer, anti-microbial, anti-protozoal, antiulcer, anti-histaminic, and anti-inflammatory activities (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel therapies, including TNFneutralizing antibodies, have demonstrated efficacy in improving mucosal healing, but their side effects and toxicity remain major clinical concerns (21). Therefore, the development of medicinal plants or their active components with minimum adverse reactions is becoming an increasingly attractive approach in the management of IBD patients (26,27). Chalcones belong to the flavonoid family, which possess a variety of biological and pharmacological properties, including antioxidant, cytotoxic, anti-cancer, anti-microbial, anti-protozoal, antiulcer, anti-histaminic, and anti-inflammatory activities (24).…”
Section: Discussionmentioning
confidence: 99%
“…Excess or inappropriate activation of NF-B has been observed in IBD patients and experimental IBD animal models (2). It has been demonstrated that the blockade of NF-B activation with flavanoid agents might be an effective strategy in abrogating experimental IBD (6,26). The most abundant form of NF-B in cells is the p50/p65 heterodimer, which is normally sequestered in the cytoplasm by binding to the inhibitory protein A B IB␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New therapeutic alternatives are in need. In addition, the long-term use of the pharmaceutical drugs results in numerous side effects [8]. So, new therapies such as the nutritional ones, especially those with antioxidant properties are suggested for the treatment of such disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for thousands of years as a food addictive in India. Due to its pharmacological effects, recently many researches have focused on its antioxidant, anti-inflammatory and anti-tumorigenic properties (Bandyopadhyay, 2014;Vecchi Brumatti et al, 2014;El-Bahr, 2015;Shanmugam et al, 2015). Numerous works prove that cur exerts strong anticancer effects against a far ranging of human cancer cells, including breast cancer, lung cancer and HCC (Jia et al, 2014;Chen et al, 2015;Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%